Thyroid Hormones Interaction With Immune Response, Inflammation and Non-thyroidal Illness Syndrome - De Luca, Roberto; Davis, Paul J.; Lin, Hung-Yun; Gionfra, Fabio; Percario, Zulema A.; Affabris, Elisabetta; Pedersen, Jens Z.; Marchese, Cinzia; Trivedi, Pankaj; Anastasiadou, Eleni; Negro, Roberto; Incerpi, Sandra (Frontiers in Cell and Developmental Biology, 2021)
The interdependence between thyroid hormones (THs), namely thyroxine and triiodothyronine, and immune system is nowadays well recognized, although not yet fully explored. Synthesis, conversion to a bioactive form and release of THs in the circulation are events tightly supervised by hypothalamic-pituitary-thyroid (HPT) axis. Newly synthesized THs induce leucocytes proliferation, migration, release of cytokines and antibody production, triggering an immune response against either sterile or microbial insults. However, chronic patho-physiological alterations of the immune system, such as infection and inflammation, affect HPT axis, and, as a direct consequence, THs mechanism of action. Herein, we revise the bidirectional crosstalk between THs and immune cells, required for the proper immune system feedback response among diverse circumstances. Available circulating THs do traffic in two distinct ways depending on the metabolic condition. Mechanistically, internalized THs form a stable complex with their specific receptors, which, upon direct or indirect binding to DNA, triggers a genomic response by activating transcriptional factors, such as those belonging to the Wnt/β-catenin pathway. Alternatively, THs engage integrin αvβ3 receptor on cell membrane and trigger a non-genomic response, which can also signal to the nucleus. In addition, we highlight THs-dependent inflammasome complex modulation and describe new crucial pathways involved in microRNAs regulation by THs, in physiological and patho-physiological conditions, which modify HPT axis and THs performances. Finally, we focus on the non-thyroidal illness syndrome in which HPT axis is altered and in turn, affects circulating levels of T3 as reported in viral infections, particularly, in immunocompromised patients infected with human immunodeficiency virus.